Work Engagement and Gender of Academic Staff in Colleges - Girija, S.; Sabarirajan, K.K. (International Journal of Psychosocial Rehabilitation, 2020)
The paper determine the effects on the work engagement of gender in the stage of the professors at college .The effect is determined by an empirical study consists of 154 educational staff members as of Sri Saradha Gangadharan Arts and Science College and Achariya Arts and Science College of Puducherry region, using the independent samples test. Information be analyse by SPSS software (version 23.0).An interpretation reveal that the work engagement level Female professors are considerably improved than that of the Men professors in the example institution.